2019
DOI: 10.1111/cbdd.13471
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 receptor ligands by hybrid virtual screening, docking, molecular dynamics simulations, and investigation of their biological effects

Abstract: Histamine H3 receptors (H3R), belonging to G‐protein coupled receptors (GPCR) class A superfamily, are responsible for modulating the release of histamine as well as of other neurotransmitters by a negative feedback mechanism mainly in the central nervous system (CNS). These receptors have gained increased attention as therapeutic target for several CNS related neurological diseases. In the current study, we aimed to identify novel H3R ligands using in silico virtual screening methods. To this end, a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 68 publications
(85 reference statements)
0
35
0
Order By: Relevance
“…Briefly, a combination of structure‐ and ligand‐based approaches was applied to search compounds from ZINC library on the homology model of the human H 3 R. Following the screening, the molecules were also inspected for drug‐likeness and ADME properties. Furthermore, the results of binding assays on selected compounds demonstrated that two compounds (i.e., compounds 3 and 4 ) were capable of binding to histamine H 3 Rs with K i values in submicromolar concentration range (Ghamari et al, ). In the current study, dual inhibitory activity of these compounds on H 3 Rs and cholinesterase enzymes was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, a combination of structure‐ and ligand‐based approaches was applied to search compounds from ZINC library on the homology model of the human H 3 R. Following the screening, the molecules were also inspected for drug‐likeness and ADME properties. Furthermore, the results of binding assays on selected compounds demonstrated that two compounds (i.e., compounds 3 and 4 ) were capable of binding to histamine H 3 Rs with K i values in submicromolar concentration range (Ghamari et al, ). In the current study, dual inhibitory activity of these compounds on H 3 Rs and cholinesterase enzymes was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GI 50 values, the cytotoxic effect is more evident for compound 3 compared to the reference compound DX and therefore in agreement with the previously predicted in silico toxic potential. Based on the scale of toxicity alert, compound 4 was predicted to be a safe compound in comparison with compound 3 (Ghamari et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghamari et al 62 built a 3D model of human and rat H3R (with N-ter absent and with ICL3 modeled as the lysozyme fusion protein in the crystal structure) by the homology comparative approach using the M3 muscarinic acetylcholine receptor in complex with tiotropium, a potent muscarinic inverse agonist (PDB Code 4DAJ). Thus, the model, just like the template receptor, is in the inactivated state.…”
Section: Discussionmentioning
confidence: 99%